A CASE STUDY ON THE SPATIAL PRACTICES OF CONSTRUCTION SITE WORKERS' QUARTERS IN KLANG VALLEY, MALAYSIA - Ng, Veronica; Liang, Lok Mei; Mari, TamilSalvi; Srirangam, Sucharita; Dasgupta, Anindita (PLANNING MALAYSIA, 2024)
This paper examines the spatial practices of construction worker housing in construction sites. In recent years, several standards and guidelines, such as MS 2593:2015 and Act 446, were implemented to improve the living environment of workers' temporary accommodation. Despite that, there is a lack of focus on the sociality of spaces as the design of these accommodations adhered to only basic spatial requirements. This resulted in prolonged issues of workers’ poor living environment being unresolved. A qualitative study using physical trace observation was conducted in a construction workers' accommodation located within an urban construction site in Klang Valley, Malaysia. Spatial observations were conducted in private areas, such as the bedrooms and the common areas, including the kitchen and dining spaces. This study reinforces the spatial practices of negotiation within the contested spaces of the temporary accommodation through the dynamic and fluid functional re-appropriation of spaces in the common and private spaces and the expansion of personal territory at both macro and micro levels.